The Influence of Principal Leadership Style and Professional Competence on Teachers' Teaching Skills in Tomohon City - ⁠Patrisia Lembong; Viktory N. J. Rotty; Elni J. Usoh; Romi J. Mongdong (International Journal of Information Technology and Education, 2026)
Teacher quality is a cornerstone of educational excellence, and teaching skill, the practical ability to plan, implement, manage, and evaluate learning effectively, remains a critical yet underexplored outcome variable in Indonesian school management research. Empirical evidence consistently highlights that both school leadership and teacher professional competence are key determinants of instructional quality, yet their combined influence on teaching skills has received limited quantitative investigation, particularly in the North Sulawesi regional context. This study aimed to examine the influence of principal leadership style and professional competence, both individually and simultaneously, on teachers' teaching skills in senior high schools in Tomohon City. This research used A quantitative research design, with simple and multiple regression analysis was employed. A proportionate stratified random sample of 106 teachers was drawn from a population of 145 teachers across five senior high schools in Tomohon City. Data were collected using validated Likert-scale questionnaires (Cronbach's α: 0.942, 0.812, and 0.885 for teaching skill, leadership style, and professional competence, respectively) and analyzed using SPSS version 25. The results of this research are that principal leadership style significantly influenced teaching skills (r = 0.597; R² = 0.356; F = 57.458; p < 0.001), explaining 35.6% of the variance. Professional competence demonstrated a stronger individual effect (r = 0.660; R² = 0.435; F = 80.054; p < 0.001), accounting for 43.5% of the variance. When both predictors were included simultaneously in a multiple regression model, they jointly explained 50.8% of the variance in teaching skills (R = 0.713; R² = 0.508; F = 53.211; p < 0.001), with the regression equation Ŷ = 6.468 + 0.293(X₁) + 0.536(X₂). This study concluded that both principal leadership style and teacher professional competence are significant and positive predictors of teaching skills, with the combined model providing the strongest explanatory power. This study implies that school policymakers and principals should adopt a synergistic approach that simultaneously strengthens adaptive leadership practices and invests in continuous professional competence development programs to optimally enhance classroom teaching quality.